Uji Bakteriologis Air Minum Isi Ulang di Kecamatan Lemahwungkuk Kota Cirebon - Sopiana, Anisa; Fitriani, Hikmah; Indrakusuma, Moh. Erwin (Syntax Literate, 2025)
Background: Refill drinking water is widely used by the public due to its accessibility and affordability. However, improper treatment processes can lead to bacteriological contamination, particularly by Escherichia coli and Coliform bacteria, which can cause diseases such as diarrhea. Aim: To identify the bacteriological content of Escherichia coli and Coliform in refill drinking water in Lemahwungkuk District, Cirebon City. Method: This study employed a descriptive method using purposive sampling techniques. A total of 8 samples were collected from refilled drinking water depots in 4 urban villages. Each sample was tested in four repetitions using various laboratory tests, including Nutrient Agar, Mac Conkey Agar, Gram Staining, IMVIC, and TSIA for identification of Escherichia coli and Coliform bacteria. Results: Mac Conkey Agar test results showed lactose fermenters in all samples, but Escherichia coli and Coliform were not detected. Gram staining revealed the presence of Gram-positive bacteria. IMVIC test results showed Indole (-), Methyl Red (-), Voges Proskauer (-), and variable Citrate results. TSIA test showed Alkaline/Alkaline results with Gas (+) in some samples. Conclusion: No Escherichia coli or Coliform bacteria were found in any of the samples, but Gram-positive bacteria were detected, indicating microbiological contamination in refill drinking water.